Laparoscopic repair of hernia in children: Comparison between ligation and nonligation of sac - Nitin Pant; Satish Kumar Aggarwal; Simmi K Ratan (Wolters Kluwer Medknow Publications, 2014)
Aim: The essence of the current techniques of laparoscopic hernia repair in children is suture ligation of the neck of the hernia sac at the deep ring with or without its transection. Some studies show that during open hernia repair, after transection at the neck it can be left unsutured without any consequence. This study was aimed to see if the same holds true for laparoscopic hernia repair. Materials and Methods: Sixty patients (52 boys and eight girls, 12-144 months) with indirect inguinal hernia were randomized for laparoscopic repair either by transection of the sac alone (Group I) or transection plus suture ligation of sac at the neck (Group II). Outcome was assessed in terms of time taken for surgery, recurrence, and other complications. Result: Thirty-eight hernia units in 28 patients were repaired by transection alone (Group I) and 34 hernia units in 29 patients were repaired by transection and suture ligation (Group II). Three patients were found to have no hernia on laparoscopy. Recurrence rate and other complications were not significantly different in the two groups. All recurrences occurred in hernias with ring size more than 10 mm. Conclusion: Laparoscopic repair of hernia by circumferential incision of the peritoneum at the deep ring is as effective as incision plus ligation of the sac.